Characterisation of bario rice flour and its potential application in the development of gluten-free bread - Macdalyna Esther Ronie (2023)
Gluten-free grains have been intensively studied as alternatives to wheat flour. Bario rice (Oryza sativa L.), an indigenous crop from Sarawak, Malaysia, is noted for its excellent aroma and taste. These cultivars were obtained from Bario Highland, Sarawak (3°44′6″N 115°28′45″E). In this research, Bario rice was ground to produce rice flour which was characterised by its nutritional, phytochemical and antioxidant properties, physical and functional properties, and the best rice flour was utilised in the development of gluten-free bread with the utilisation of rice flour between 70% to 100% complemented with potato starch. Four Bario rice varieties were analysed against the control sample (TQR rice) consisting of non-pigmented and pigmented rice, namely Bario Adan Halus (white) and Bario Tuan (brown), Bario Celum (black), also Bario Merah Sederhana (red), respectively. The results revealed that pigmented Bario rice flour contained significantly higher (p<0.05) ash, crude fat, and crude fibre content than non-pigmented. The crude protein content, for all rice flour samples, was in the range of 6.89% to 9.43%. Bario Tuan and Bario Merah Sederhana showed the lowest (p<0.05) carbohydrate content among all. The mineral content of Bario rice flour was significantly greater (p<0.05) in magnesium, potassium, and zinc content compared to the control. All Bario rice flours had high amylose content (26.67% - 36.52%), positively impacting loaf volume. Pigmented Bario rice flour exhibited greater phytochemical characteristics based on total phenolic content and total flavonoid content and also indicated higher (p<0.05) antioxidant properties in 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity compared to non-pigmented. The swelling capacity was significantly (p<0.05) high in non-pigmented rice flour. The foaming capacity of Bario Tuan (5.59%) was comparable with the control sample (5.63%), which this parameter generally depends on the solubility of the protein. The least gelation concentration ranged from 10% to 20%, and Bario Merah Sederhana exhibited the lowest value, 10% which implies a better gelling capacity. The final gelatinisation temperature of Bario Tuan (84.45 ℃) and Bario Merah Sederhana (84.38 ℃) were higher among all samples, and gelatinisation temperature has a directly proportional relationship to the specific volume of bread. Bario Merah Sederhana was chosen to be utilised in gluten-free bread development, against wheat bread. The ash and crude fibre content were generally higher in gluten-free bread, in contrast, lower in carbohydrate content compared to wheat bread. The texture profile analysis of gluten-free dough and bread appeared to be softer in F4 (70% rice flour with 30% potato starch). The sensory evaluation showed the F4 received the highest overall acceptability among gluten-free bread. In conclusion, due to its physical and functional, nutritional, phytochemicals and antioxidants, Bario rice flour, especially the pigmented types, has shown potential as a gluten-free flour alternative in the production of gluten-free bread. Besides, the addition of potato starch to rice flour increased the texture and general acceptance of gluten-free bread especially by 30%. As a recommendation, future studies might investigate the amino acid profiles of Bario rice varieties which could provide further insight into its functional behaviour in product development.